2017
DOI: 10.1177/096369351702600204
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Properties of Graphite/Antimony Composites Based on Coal Tar Pitch

Abstract: Coal tar pitch is used as the raw material to prepare graphite/antimony composites, of which the mechanical performance, microstructure, element composition and tribological performance are investigated. Results indicate that the composite density, shore hardness, flexural strength, compression strength and porosity are 2.38g/cm 3 ,103.10Hs,91.65MPa,290.5MPa, and 0.65% respectively, representing physical property improvement of 17.65%-28.75%. In addition to C, the major composite elements are Sb, Si, Al and S,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…In recent years, the study of synthetic graphite and its applications has become a hot topic in the research field. , A range of carbon sources with high carbon content and fewer impurities, e.g., petroleum coke, coal tar pitch, anthracite, and bituminous coal, , were taken to prepare the synthetic graphite. Specifically, anthracite is one of the favorable resources for preparing synthetic graphite owing to its lower ash content and oxygen-containing functional groups. , Studies regarding coal-based synthetic graphite suggested that, with a lower rising rate of temperature and a higher final temperature, the obtained synthetic graphite tends to have a higher graphitization degree and perfect crystalline structure. , More importantly, the thermodynamics and kinetics of chemical reactions during the graphitization process of anthracite were investigated .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the study of synthetic graphite and its applications has become a hot topic in the research field. , A range of carbon sources with high carbon content and fewer impurities, e.g., petroleum coke, coal tar pitch, anthracite, and bituminous coal, , were taken to prepare the synthetic graphite. Specifically, anthracite is one of the favorable resources for preparing synthetic graphite owing to its lower ash content and oxygen-containing functional groups. , Studies regarding coal-based synthetic graphite suggested that, with a lower rising rate of temperature and a higher final temperature, the obtained synthetic graphite tends to have a higher graphitization degree and perfect crystalline structure. , More importantly, the thermodynamics and kinetics of chemical reactions during the graphitization process of anthracite were investigated .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the study of synthetic graphite and its applications has become a hot topic in the research field. 11 , 12 A range of carbon sources with high carbon content and fewer impurities, e.g., petroleum coke, 13 coal tar pitch, 14 anthracite, 15 and bituminous coal, 12 , 16 were taken to prepare the synthetic graphite. Specifically, anthracite is one of the favorable resources for preparing synthetic graphite owing to its lower ash content and oxygen-containing functional groups.…”
Section: Introductionmentioning
confidence: 99%